Kansas Myriapoda - Norton, J.B. (My University, 1897)
Introduction: Last summer, while working on the collection of Myriapoda in the Kansas Agricultural College museum, my aroused interest led to a somewhat extended collection of Riley County forms of this group. This collection, together with one from Topeka collected by C. W. Pape ’95 during the past year at different times, and the species mentioned by F. W. Cragin and a few in other papers by Wood, Bollman and others forms the basis of the descriptive list in this paper. This division of the Arthropoda is not of great economic importance in this locality. The true Myriapods – Diplopoda – are found feeding only on decayed vegetable matter and are never very numerous in any situation. They are perfectly harmless but are objectionable on account of their disagreeable odor. The Syngnatha, or centipedes of various kinds, are predaceous, living on insects, spiders etc. Perhaps, on account of their abundance, they may be of economic importance—at least as much so as the predaceous insects. All of this group have more or less developed poison glands in the claws of their prehensorial legs. The small Geophilidae can raise quite a lump by their bite in a tender spot.
Citation: Norton, J.B. Kansas Myriapoda. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Kansas; Riley county; Entomology; Myriapoda; Theses; Manuscripts (documents)